Explosion accident analysis of ultra-high-speed grinding wheel. (April 2021) - Wu, Yao; Lu, Pan; Lin, Feihong; Bao, Wencheng; Qu, Meina; Li, Ping; He, Hao
Highlights: A method was suggested to assessing the accidental explosion of an ultra-high-speed grinding wheel. Microcracks on the working layer, powder metallurgy defect in the transition layers, and adhesive failure between matrix and abrasive layer can increase the risk of grinding wheel blasting. Abstract: Ultra-high-speed grinding is an effective technology used in high-performance precision grinding of engineering ceramic, glass, carbide, titanium alloy, stainless steel and other difficult materials. In ultra-high-speed grinding, grinding wheel speed reaches 150–300 m/s or higher, comparable to muzzle velocity of a bullet. When the working grinding wheel is broken during high-speed rotation, the flying speed of the debris is even higher than the muzzle velocity of a bullet. This condition poses a threat to the operator's safety and damages the machine tool, resulting in large economic losses. This study assessed the accidental explosion of an ultra-high-speed bronze bond CBN grinding wheel in actual working process. Based on fractography analysis of explosion grinding wheel and numerical analysis of the grinding wheel safety caused by centrifugal force, grinding forces, and adhesive failure between the grinding wheel matrix and abrasive layer, this study investigated the causes of the explosion of an ultra-high-speed grinding wheel. The following reasons for the accident were found: (1) defects appear at thread holes in the abrasive layer of the grinding wheel, (2) powder metallurgy defects in the transition layer of the grinding wheel, (3) fatigue cracks appear along the interface between the bond and grain under the centrifugal and grinding forces, and (4) adhesive failure at the interface between the grinding wheel matrix and abrasive layer.